The greening of economic policy reform: principles - Warford, Jeremy J.; Munasinghe, Mohan; Cruz, Wilfrido; World Bank. (Washington, D.C. : World Bank, 1997)
This book shows that there are significant payoffs in attempting to understand such impacts better and to act upon them
Volume 1
Includes bibliographical references.
osc 27/10/2021
Loans
Keywords: Sustainable development; Economic policy